The correlation of the intestinal with pharyngeal microbiota in early neonates - Wang, Xuejuan; Shao, Zhiying; Zhu, Minrong; Li, Bingjie; You, Mingyu; Chen, Xiaoqing (Frontiers in Microbiology, 2023)
Introduction The gut-lung axis has long been recognized as an important mechanism affecting intestinal and lung immunity. Still, few studies have examined the correlation between the intestinal and pharyngeal microbiota in early neonates, especially when feeding patterns are one of the main drivers of microbiota development. Methods To explore the composition and function of intestinal and pharyngeal microbiota and to analyze the effect of limited formula feeding on the initial microbiota colonization in early full-term neonates, we characterized the stool and oropharyngeal microbiota of 20 healthy full-term newborns sampled on days 0 and 5–7 after birth using 16S rRNA gene sequencing. Based on the sequencing results, a comparison was made of the compositions and functions of the intestinal and oropharyngeal microbiota for analysis. Results and discussion At the phylum level, Firmicutes, Actinobacteria, Proteobacteria, and Bacteroidetes were the most abundant in both niches. At the genus level, the species of pioneer bacteria were rich in the intestine and oropharynx but low in abundance on day 0. On days 5–7, Bifidobacterium (25.40%) and Escherichia-Shigella (22.16%) were dominant in the intestine, while Streptococcus (38.40%) and Staphylococcus (23.13%) were dominant in the oropharynx. There were eight core bacteria genera in the intestine and oropharynx on days 5–7, which were Bifidobacterium, Escherichia-Shigella, Staphylococcus, Streptococcus, Bacteroides, Parabacteroides, Rothia, and Acinetobacter. As indicated by PICRUSt analysis, on days 5–7, the intestinal microbiota was more predictive than the oropharyngeal microbiota in transcription, metabolism, cell motility, cellular processes and signaling, and organismal system function in the KEGG pathway. Compared to exclusive breastfeeding, limited formula feeding (40–60%) had no significant effect on the neonatal intestinal and oropharyngeal microbiota composition during the initial colonization period. Our results suggest that the initial colonization of microbiota is closely related to the ecological niche environment in the intestine and oropharynx, with their core microbiota being closely correlated. We found that early limited formula feeding could not significantly affect the initial colonization of microbiota in the intestine and oropharynx.